2014
DOI: 10.1615/critreveukaryotgeneexpr.2013006875
|View full text |Cite
|
Sign up to set email alerts
|

Review of Poly (ADP-ribose) Polymerase (PARP) Mechanisms of Action and Rationale for Targeting in Cancer and Other Diseases

Abstract: Poly (ADP-ribose) polymerases (PARPs) are a family of related enzymes that share the ability to catalyze the transfer of ADP-ribose to target proteins. PARPs play an important role in various cellular processes, including modulation of chromatin structure, transcription, replication, recombination, and DNA repair. The role of PARP proteins in DNA repair is of particular interest, in view of the finding that certain tumors defective in homologous recombination mechanisms, may rely on PARP-mediated DNA repair fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
371
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(385 citation statements)
references
References 86 publications
9
371
0
5
Order By: Relevance
“…Poly ADP ribose polymerase (PARP) is an essential mediator of BER that targets single-strand breaks (SSBs) induced by DNA damage and recruits BER complex proteins (Morales et al, 2014). The peak of DNA demethylation upon 10 days of Tet2 restoration to cKit + cells correlated with increased expression of Parp and Gadd45 (Figure 7D), whose gene products function in DNA demethylation (Barreto et al, 2007; Ciccarone et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Poly ADP ribose polymerase (PARP) is an essential mediator of BER that targets single-strand breaks (SSBs) induced by DNA damage and recruits BER complex proteins (Morales et al, 2014). The peak of DNA demethylation upon 10 days of Tet2 restoration to cKit + cells correlated with increased expression of Parp and Gadd45 (Figure 7D), whose gene products function in DNA demethylation (Barreto et al, 2007; Ciccarone et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research has revealed numerous PARP1 functions spanning a diverse array of nuclear processes, including DNA damage repair (2)(3)(4)(5), chromatin remodeling (6), transcriptional regulation (6), telomere maintenance (7), and cell death (8). Owing primarily to the role of PARP1 (and the related but less abundant PARP2 and PARP3) in DNA damage repair, a number of PARP inhibitors are undergoing clinical development as anticancer agents with a focus on tumors with impaired homologous recombination (HR) capability and on combination regimens with DNA-damaging chemotherapy or radiation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Again, colony survival assays confirmed this hypothesis although it should be noted that the effect was less significant than observed at the lower oxygen level. This is perhaps not surprising given the role of PARP in the response to replication stress [79]. However, our data demonstrating that proliferating hypoxic cells are sensitive to PARP inhibition are extremely promising clinically, as these cells are more abundant and more accessible in a solid tumour.…”
Section: Targeting Tumour Hypoxia Through Parp Inhibitionmentioning
confidence: 75%